Causes of death in a contemporary adult congenital heart disease cohort. Issue 20 (17th April 2018) - Yu, Christopher; Moore, Benjamin M; Kotchetkova, Irina; Cordina, Rachael L; Celermajer, David S
Abstract : Objective: The life expectancy of patients with congenital heart disease (CHD) has significantly improved with advances in their paediatric medical care. Mortality patterns are changing as a result. Our study aims to describe survival and causes of death in a contemporary cohort of adult patients with CHD. Methods: We reviewed 3068 patients in our adult CHD database (age ≥16 years, seen at least once in our centre between 2000 and 2015), and documented the number and causes of death, via Australia's National Death Index. Survival and mortality patterns were analysed by complexity of CHD and by underlying congenital diagnosis. Results: Our cohort comprised 3068 adult patients (53% male). The distribution of patients (per the Bethesda classification) was 47% simple, 34% moderate and 18% complex (1% not classifiable). Over a median follow-up of 6.2 years (IQR 3.5–10.4), 341 patients (11%) died with an incidence of 0.4 deaths/100 patient years (py). Survival was significantly worse with increasing complexity of CHD (p<0.001); mortality rate in the simple group was 0.3 deaths/100 py with a median age of death 70 years, and in the complex group was 1.0 death/100 py with a median age of death 34 years. Overall, non-cardiac causes of death outnumbered cardiac causes, at 54% and 46%, respectively. The leading single cause of death was heart failure (17%), followed by malignancy (13%). Simple adult CHD patients mostly died due to non-cardiac causes such as malignancy. Perioperative mortality only accounted for 5% of deaths. Conclusions: Premature death is common in adults with CHD. Although heart failure remains the most common cause of death, in the contemporary era in a specialist CHD centre, non-cardiac related deaths outnumber cardiac deaths, particularly in those with simple CHD lesions.